Anesthetic Management of a Pediatric Patient with Factor VII Deficiency for Emergency Nasal Foreign Body Removal - M, Lakshmi; M , Akilandeswari; Kodali V, Rajesh Kumar (Journal of Neonatal Surgery, 2025)
A 3-year-old male child with known Factor VII deficiency presented with recurrent nasal bleeding, decreased oral intake, and sleep disturbances. Nasal endoscopy revealed a foreign body with granulation tissue. Preoperative coagulation profile showed prolonged PT (66.2 sec) and INR (5.61), necessitating fresh frozen plasma (FFP) transfusion before surgery. The child underwent general anesthesia with careful perioperative monitoring. Postoperatively, the child was shifted to ICU for ventilatory support. This case highlights the challenges in managing congenital bleeding disorders in Pediatric emergencies.